2021
DOI: 10.1038/s41598-020-80820-1
|View full text |Cite
|
Sign up to set email alerts
|

Coupling machine learning and crop modeling improves crop yield prediction in the US Corn Belt

Abstract: This study investigates whether coupling crop modeling and machine learning (ML) improves corn yield predictions in the US Corn Belt. The main objectives are to explore whether a hybrid approach (crop modeling + ML) would result in better predictions, investigate which combinations of hybrid models provide the most accurate predictions, and determine the features from the crop modeling that are most effective to be integrated with ML for corn yield prediction. Five ML models (linear regression, LASSO, LightGBM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
129
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(130 citation statements)
references
References 76 publications
1
129
0
Order By: Relevance
“…In a recent study, Shahhosseini et al [60] showed that adding physics-based crop model variables as input features to ML models can improve the performance of ML models by 29% on average in the US Corn Belt. They compared the performances of several ML models such as RF, linear regression (LR), least absolute shrinkage and selection operator (LASSO) regression, Light Gradient Boost (LightGBM), Extreme Gradient Boost (XGBoost), and also an ensemble of them to investigate their added value individually and in combination.…”
Section: Crop Yield Predictionmentioning
confidence: 99%
“…In a recent study, Shahhosseini et al [60] showed that adding physics-based crop model variables as input features to ML models can improve the performance of ML models by 29% on average in the US Corn Belt. They compared the performances of several ML models such as RF, linear regression (LR), least absolute shrinkage and selection operator (LASSO) regression, Light Gradient Boost (LightGBM), Extreme Gradient Boost (XGBoost), and also an ensemble of them to investigate their added value individually and in combination.…”
Section: Crop Yield Predictionmentioning
confidence: 99%
“…AI4Water is built on top of Scikit-learn, CatBoost, XGBoost, and LightGBM libraries to build classical machine learning models. These models have been used in several hydrological studies (Ni et al, 2020;Huang et al, 2019;Shahhosseini et al, 2021). To build deep learning models using neural networks, AI4Water uses a popular deep learning platform called TensorFlow (Abadi et al, 2016).…”
Section: Workflow and Model Structurementioning
confidence: 99%
“…Some other studies have made additional advancement and created hybrid crop model-ML methodologies by using crop model outputs as inputs to a ML model ( Everingham et al, 2016 ; Feng et al, 2019 ). In a recent study, Shahhosseini et al (2021) designed a hybrid crop model-ML ensemble framework, in which a crop modeling framework (APSIM) was used to provide additional inputs to the yield prediction task (For more information about APSIM refer to https://www.apsim.info/ ). The results demonstrated that coupling APSIM and ML could improve ML performance up to 29% compared to ML alone.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is always a tradeoff between the model complexity and its interpretability, the recent complex models could better capture all kinds of associations such as linear and nonlinear relationships between the variables associated with the crop yields, resulting in more accurate predictions and subsequently better helping decision makers ( Chlingaryan et al, 2018 ). These models span from models as simple as linear regression, k-nearest neighbor, and regression trees ( González Sánchez et al, 2014 ; Mupangwa et al, 2020 ), to more complex methods such as support vector machines ( Stas et al, 2016 ), homogenous ensemble models ( Vincenzi et al, 2011 ; Fukuda et al, 2013 ; Heremans et al, 2015 ; Jeong et al, 2016 ; Shahhosseini et al, 2019 ), heterogenous ensemble models ( Cai et al, 2017 ; Shahhosseini et al, 2020 , 2021 ), and deep neural networks ( Liu et al, 2001 ; Drummond et al, 2003 ; Jiang et al, 2004 , 2020 ; Pantazi et al, 2016 ; You et al, 2017 ; Crane-Droesch, 2018 ; Wang et al, 2018 ; Khaki and Wang, 2019 ; Kim et al, 2019 ; Yang et al, 2019 ; Khaki et al, 2020a , b ). Homogeneous ensemble models are the models created using same-type base learners, while the base learners in the heterogenous ensemble models are different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation